Wheezy adult with chicken bone in the chest - Nagabhushna Rao, Bhavana Venkata; Vatti, Narmada; Tadikonda, Balaraju; Ponnapalli, Srinivasa Perraju (International Journal of Research in Medical Sciences, 2018)
A large foreign body aspiration in a healthy adult is rare in the literature. It is a frequent problem in children and adolescents. Adults are affected in altered sensorium, either due to sedation or neurological problems. Acute upper airway obstruction though rare in adults requires establishment of an airway using Laryngoscope or rigid bronchoscope. At times we have to recourse to tracheostomy to save the life. Foreign body often travels down the right sided airways, here we present a case of 30mm Chicken bone being lodged in the left main bronchus. The patient presented with unremitting cough and normal chest skiagram. Monophonic wheeze on auscultation and focused attention on the patient narration made us clinch the diagnosis. New onset wheezy chest or unremitting chronic airway disease on adequate therapy, with history of choking needs special attention. The CT scan is a better modality of the investigation. Three dimensional CT with multi-slice virtual bronchoscopy is advantageous. We discussed foreign body aspirations in adults, the various causes and presentations. Fiber optic bronchoscopy is the ideal method for visualization and extraction of non-life-threatening foreign bodies in adults. Once a foreign body is identified, it has to be removed as early as possible. Retained foreign bodies can precipitate many complications related to infection and inflammation. At rare incidence we may have to resort to thoracotomy to remove a complicated foreign body.